A novel upcycling technique of recycled cement paste powder by a two-step carbonation process. (25th March 2021) - Fang, Xiaoliang; Xuan, Dongxing; Zhan, Baojian; Li, Weifeng; Poon, Chi Sun
Abstract: The construction industry, being a major consumer of natural resources and energy, is eager to develop novel upcycling techniques for converting secondary resources derived from concrete waste into new and value-added products. However, upcycling of demolished concrete waste is limited by the shortage of practical and economical techniques. This paper presents the development of an innovative upcycling technique to convert recycled fine cement waste to a Ca-rich residue and a Si-rich gel by using a two-step carbonation process. This two-step process involves i) fine recycled cement powder reacting with a Na2 CO3 solution to precipitate a calcium-rich residue and ii) after filtration, the filtrate containing Na2 SiO3 and NaOH was subjected to a flow-through CO2 gas carbonation to obtain the suspension with a silica-rich gel and the Na2 CO3 solution. The physical and chemical properties of the precipitated products from both steps were analyzed by a range of techniques, including particle size distribution, Fourier-transformed infrared spectroscopy (FTIR), X-ray powder diffraction (XRD), X-ray fluorescence spectroscopy (XRF), thermogravimetric analysis (TGA), nuclear magnetic resonance (NMR), and scanning electron microscopy (SEM). The results indicated that the proposed technique was able to successfully convert recycled cement paste powder to two new value-added reaction products, containing calcite and silica gel. Graphical abstract: Image 1